Upaya Pemanfaatan Sampah Plastik Kelompok Ibu-Ibu Dasawisama Gladiol 161 di Perumahan Magersari Permai, Kabupaten Sidoarjo - Budiarti, Wiwik; Susilowati, Sri; Farida, Ilya (Jurnal Komunikasi Profesional, 2018)
The purpose of the community partnership program activities (PKM) is the empower the target audience to have knowledge about the importance of utilizing leisure time with positive activities that can bring profit or additional income, namely by making handicrafts made from plastic waste. Utilizatio of plastic waste is still rarely done in area where citizens do not pay attention to things such as craft creativity by using waste at the Magersari Permai housing in Sidoarjo Regency there is also no attempt to use plastic waste that is processed into handicraft. In addition, there are still many young mothers  who are still productive but do not have jobs only as housewives  who have a lot of free time, which has been used a lot of unproductive things  such as watching TV or chatting with neighborn. The benefit of this PKM activity is that the holding  of this community service is expected to be useful or useful for 1) Increasing the knowledge of mothers about the importance of utilizing free time with beneficial and beneficial  activities 2) Increasing the skills of mothers in making craft. 3) Maintaining and creating environmental hygiene by utilizing plastic waste into handicrafts that have a selling value that can increase  the familys economic income.Keywords: Handicrafts, Plastic, Waste, and Creativity.